2021
DOI: 10.1111/bjd.19713
|View full text |Cite
|
Sign up to set email alerts
|

Trends in body mass index before and after diagnosis of hidradenitis suppurativa

Abstract: Background A temporal relationship between hidradenitis suppurativa (HS) and obesity has not been established. Objectives To compare baseline body mass index (BMI) and change in BMI for patients with HS and controls before and after diagnosis. Methods We performed a retrospective case-control analysis of 1284 patients with HS and controls matched for age, sex, race and calendar year between 1 January 1999 and 9 September 2019. BMI 7 years prior to first HS diagnosis, and rate of BMI change, were compared for p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Wright, S. 93 Retrospective case-control analysis of 1284 patients with HS and controls matched for age, sex, and race.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wright, S. 93 Retrospective case-control analysis of 1284 patients with HS and controls matched for age, sex, and race.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 90% of patients are current or former smokers, and smoking appears to contribute to disease onset and progression 95 . The underlying mechanisms are still not clear, but nicotine is known to promote proinflammatory cytokines, induce epidermal hyperplasia, and interfere with the microbiome 93 . Obesity might contribute to HS pathogenesis through subclinical inflammation, metabolic changes, and friction 99,100 .…”
Section: Thyroid Diseasementioning
confidence: 99%
“…Quite recently, a retrospective analysis of 1284 HS patients relative to age-, sex- and race-matched controls (enrolled between 1999 and 2019) was conducted by Wright et al The researchers found that baseline BMI was higher among HS patients than controls ( p < 0.001). This difference was larger for women than men [ 66 ]. Individual patient data from the PIONEER 1 and PIONEER 2 studies revealed that an increase in BMI (overweight and obese category) was associated with decreased odds of achieving Hidradenitis Suppurativa Clinical Response (HiSCR).…”
Section: Hs and Dietmentioning
confidence: 99%
“…Dear Editor, There is a significant overlap between comorbidities associated with HS 1,2 and severe COVID-19 illness. [3][4][5] Additionally, immunomodulating medications for HS may influence the course of COVID-19 illness. We sought to compare the risk of COVID-19-related hospitalization between HS patients and controls and to compare risk according to immunomodulator use.…”
mentioning
confidence: 99%